An analysis of the shadow economy in Malta: A currency demand and MIMIC model approach - Tiziana Marie Gauci; Noel Rapa (Central Bank of Malta, 2020)
The paper applies two commonly used methods in the literature to estimate the shadow economy in Malta, the Currency Demand Approach and the Multiple Indicator Multiple Causes (MIMIC) model. Given the unobservable nature of the shadow economy, estimates are surrounded by a considerable degree of uncertainty. While these two methods differ somewhat on the historical evolution of the size of the Maltese shadow economy, which in turn can be traced back to their different underlying assumptions, both suggest that it has remained relatively stable over the last decade, standing at just below 21% of official GDP in 2019. Where possible, these estimates are compared to other studies on the same subject where we find that the dynamic properties of our variable follow those found in the literature.
Keywords: C32; E26; H26; O17; 330; Shadow economy; Structural modelling; MIMIC; Currency demand approach; Malta